2001
DOI: 10.1139/v01-162
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human serum albumin with oxovanadium ions studied by FT-IR spectroscopy and gel and capillary electrophoresis

Abstract: Some oxovanadium compounds have shown potential to inhibit RNase activity, while at the same time not inhibiting DNase activity. Some vanadyl complexes also inhibit protein synthesis in rabbit reticulocytes, but induce activation of protein–tyrosine kinase. To gain an insight into the interaction of oxovanadium ions with proteins, the present study was designed to examine the bindings of VOSO4 and NaVO3 salts with human serum albumin (HSA) in aqueous solution at physiological pH with metal ion concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Gel electrophoresis results showed that a maximum of twenty VO 2+ cations is bound per HSA molecule, at two sites with different affinities. Capillary electrophoresis confirmed the existence of two major binding sites for the oxovanadium(IV) cation, whereas VO 3 -has only a very weak binding affinity 41 , consistent with previous studies. 42 IR spectroscopic analysis showed that, as a consequence of the VO 2+ /HAS interaction, major structural changes are produced at the protein secondary structure.…”
Section: Transferrin and Serum Albumin Complexessupporting
confidence: 90%
See 1 more Smart Citation
“…Gel electrophoresis results showed that a maximum of twenty VO 2+ cations is bound per HSA molecule, at two sites with different affinities. Capillary electrophoresis confirmed the existence of two major binding sites for the oxovanadium(IV) cation, whereas VO 3 -has only a very weak binding affinity 41 , consistent with previous studies. 42 IR spectroscopic analysis showed that, as a consequence of the VO 2+ /HAS interaction, major structural changes are produced at the protein secondary structure.…”
Section: Transferrin and Serum Albumin Complexessupporting
confidence: 90%
“…42 IR spectroscopic analysis showed that, as a consequence of the VO 2+ /HAS interaction, major structural changes are produced at the protein secondary structure. 41 In a recent comparative study of the binding of vanadate to HSA, human fresh frozen plasma and human transferrin, it was demonstrated that the binding capacity of HSA is about one thousandth of those of the other two systems. 43 …”
Section: Transferrin and Serum Albumin Complexesmentioning
confidence: 99%
“…This dye displacement technique has some advantages over other electrophoretic techniques in that it is faster and uses less reagent. In a CE investigation of the interactions of HSA with two herbicides, atrazine and 2,4-dichlorophenoxyacetic acid, the changes of the secondary structure could be deduced and were found to agree with the results obtained by FTIR [92]. The interaction between HSA and VO 21 or VO 3 2 was studied using CZE.…”
Section: Protein-small Molecule Interactionsupporting
confidence: 68%
“…The interaction between HSA and VO 21 or VO 3 2 was studied using CZE. VO 3 2 has only a weak binding affinity (6.0610 3 M 21 ) to HSA, but VO 21 (the reduced form of VO 3 2 ) binds to HSA with two strong affinities (K 1 = 1.2610 8 M 21 , K 2 = 8.5610 5 M 21 ) [93]. In ACE, the migration time of four compounds (warfarin, ibuprofen, surprofen, and flurbiprofen) was measured in the presence of normal or modified HSA (at tryptophan 214 or tyrosine 411).…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%
“…CE in different formats including zone electrophoresis and frontal analysis was used to a number of binding studies and investigated binding of ribonuclease and ovalbumin to agglutinin from Lens culinaris [211], drugs to human serum albumin and a 1 -acid glycoprotein [131], teicoplanin and D-Ala-D-Ala terminated peptides [212], enediynes [213], fosfatidylserine [214], and heparin [215] to BSA, anionic drugs [216] and oxybutinin to plasma proteins [217], drugs to plasma lipoproteins [218] and to subdomain III of HSA [219], porfyrin to HSA [220,221], heptamethine cyanine dye to HSA [41], phosphates to lysozyme, lactoferrin, and a-lactoglobulin [222] DNA to proteins [81], basic drugs to human a 1 -acid glycoprotein [223], further interactions of pUC19DNA and ovalbumin [224], 3'-azido-3'-deoxythymidine [225], oxovanadium ions [226], and herbicides atrazine and 2,4-dichlorophenoxyacetic acid [226] with HSA, green fluorescent fusion protein with cyclophilin [45], detection of hidden ligands that stabilize cholinesterase conformation [227], investigation of metal complexes with metallothionein in rat tissues [228], kinetic parameters of rhodanase [229], effect of oxidation of low-density lipoproteins on drug binding affinity [230], formation of a covalent conjugate between microcystin Lr and protein phosphatase 2a [231], identification of drug-binding sites in HSA [109] and modifying sites of mono-PEGylated calcitonins [232], and mapping of stereoselective recognition sites of human serum transferrin [233].…”
Section: Other Proteinsmentioning
confidence: 99%